If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -102 = -6(3 + 7x) -102 = (3 * -6 + 7x * -6) -102 = (-18 + -42x) Solving -102 = -18 + -42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42x' to each side of the equation. -102 + 42x = -18 + -42x + 42x Combine like terms: -42x + 42x = 0 -102 + 42x = -18 + 0 -102 + 42x = -18 Add '102' to each side of the equation. -102 + 102 + 42x = -18 + 102 Combine like terms: -102 + 102 = 0 0 + 42x = -18 + 102 42x = -18 + 102 Combine like terms: -18 + 102 = 84 42x = 84 Divide each side by '42'. x = 2 Simplifying x = 2
| (3x-2)/4=7 | | p-4p=24 | | -6(5+3n)=114 | | x-3x+5=12 | | X-2-3=2X-7 | | 3X-2-3=2X-7 | | -2(4-8n)=120 | | 3X-2X-3X=2X-7X | | -21=9k-2k | | 360-(5x+90)= | | 85=-5(-5-2v) | | 2(4-4x)=21+14x | | 2+5(5p+6)=232 | | 12+19x+4x^2=0 | | -6(3n+5)+5=-151 | | 5v^2-90=0 | | 2(3w-8)*(2w)=40 | | 6+2(y-4)=13 | | 2+22= | | 7.11=2(3.14)R | | 4(1+5m)=164 | | 7(2x+8)=84 | | (x-12)(x+1)=-40 | | 8(-2)-3y=-7 | | 8(-2)-3y=7 | | 4x-2=6x-8+x | | 7(5a-3)=84 | | 2(-3)-2(8)=-6 | | 2x^2+21x+40=0 | | 7(-2)-6y=-2 | | x-30.34=22.87 | | 3x^2-13x+12-y=0 |